2021
DOI: 10.1021/acs.chemrev.0c01180
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Induced “One-Pot” Click Chemistry

Abstract: Click chemistry has been established rapidly as one of the most valuable methods for the chemical transformation of complex molecules. Due to the rapid rates, clean conversions to the products, and compatibility of the reagents and reaction conditions even in complex settings, it has found applications in many molecule-oriented disciplines. From the vast landscape of click reactions, approaches have emerged in the past decade centered around oxidative processes to generate in situ highly reactive synthons from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 200 publications
0
52
0
Order By: Relevance
“…[ 9,10 ] A successful example is benefitting from the activation by ring strain in the structure of reactants, for example, cycloalkyne or cycloalkane. [ 11–15 ] Particularly, the strain‐promoted alkyne‐azide cycloaddition (SPAAC) is an outstanding member of this class owing to its excellent chemical stability, non‐toxic and mild reaction conditions, and high coupling efficiency for bio‐orthogonal conjugations. [ 16–19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9,10 ] A successful example is benefitting from the activation by ring strain in the structure of reactants, for example, cycloalkyne or cycloalkane. [ 11–15 ] Particularly, the strain‐promoted alkyne‐azide cycloaddition (SPAAC) is an outstanding member of this class owing to its excellent chemical stability, non‐toxic and mild reaction conditions, and high coupling efficiency for bio‐orthogonal conjugations. [ 16–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] A successful example is benefitting from the activation by ring strain in the structure of reactants, for example, cycloalkyne or cycloalkane. [11][12][13][14][15] Particularly, the strain-promoted alkyneazide cycloaddition (SPAAC) is an outstanding member of this class owing to its excellent chemical stability, non-toxic and mild reaction conditions, and high coupling efficiency for bio-orthogonal conjugations. [16][17][18][19] Commonly, azide derivatives are used as bio-tags in biochemistry due to easy integration with biomolecules, for example, in metabolic labeling for living cells with azido functionality, [20,21] post-synthetic modification, [22,23] and in vitro enzymatic transfer.…”
mentioning
confidence: 99%
“…Interest-ingly, different conversion efficiencies were obtained for the opioid peptides Leu-and Met-enkephalin, indicating that residues distally positioned from the site of conjugation can influence the reaction, thus pointing to the potential of high substrate specificity. We therefore expect that the current results encourage applications of nucleoapzymes in selective bioconjugation reactions of tyrosine residues, [6,27,28] and such studies are currently ongoing in our laboratories.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, we [3] and others [4] have shown that the horseradish peroxidase-mimicking hemin/G-quadruplex (hGQ) DNAzyme catalyst [5] has the ability to efficiently modify tyrosine (Tyr) residues in a variety of proteins with N-methyl luminol derivatives. [6] Applications of this hGQ DNAzyme as proteinmodifying catalyst in a switchable nanostructure showed that the modification could also be performed in more advanced settings. [3] Although the hGQ nanostructure itself provided a basic level of substrate selectivity, its conjugation to structural elements that specifically recognize a substrate could, in principle, enable a higher level of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Generally applicable approaches for artificial chemical modification of proteins are thus of great importance. Despite recent progress, [4][5][6][7] site-specific protein modification remains a major challenge, and no widely applicable approach is currently available. So far various methods have been established to derivatize specific residues in some proteins, e.g., via reactive residues in unique micro-environments, genetic incorporation of uniquely reactive or maybe even orthogonal groups, such as azides or alkynes, or by optimized reagents designed to target single residues.…”
Section: Introductionmentioning
confidence: 99%